Review of the monograph «Bugai N.F. Problems of the national policy of the Russian Federation: the state of study, the experience of regulating ethnic processes (1990s – 2015). – Moscow: Aquarium, 2022. – 694 p.» - Svetlana I. Akkieva; Alexey Кh. Abazov (Кавказология)
The review is devoted to the monograph of the famous historian N.F. Bugai. It examines the problems of the national policy of the Russian Federation in the period from the 1990s to the early 2020s. The work is based on a wide range of sources. These include published and unpublished archival materials, documents from central and local authorities, as well as an extensive body of research results on the topic. The book analyzes past events, allowing us to understand the scale of the problems that had accumulated by the beginning of the period under review. A special feature of the reviewed work is a detailed analysis of both the achievements and shortcomings faced by the Russian statehood during the period under review. This indicates the author's deep understanding of the realities of the time and problems in the field of national politics. The book presents extensive and diverse material about the peoples of Russia, as well as other ethnic groups living in the country. The article considers the role and place of civil society institutions and ethnic minorities in the system of relations in modern conditions. Special attention is paid to the author's conclusions and recommendations concerning the state national policy and the prospects for its further development.